Pewarisan Musik Krilu Di Sanggar Ratau Agung Di Desa Tunggang Kecamatan Lebong Utara Kabupaten Lebong Provinsi Bengkulu - Inka Aglisda; Syeilendra Syeilendra (SENDRATASIK UNP, 2020)
This study aims to describe or find out the inheritance of the Krilu musical instrument in Sanggar Ratau Agung in Tunggang Village, Lebong Utara District, Lebong Regency, Bengkulu Province. This research is a qualitative research. The research instrument was the researcher itself and was assisted by supporting instruments such as stationery, voice recorder, and camera. The type of data in this study was primary and secondary data. The data were collected through literature study, observation, interview, and documentation. The data analysis was conducted by collecting data, classifying data analysis, and making conclusions and suggestions. The results show that the inheritance of Krilu in Sanggar Ratau Agung in Tunggang Village, Lebong Utara District, Lebong Regency, Bengkulu Province uses an open and enculturation system. This inheritance system does not use a closed one due to the fact that there is no family from Krilu artists that can inherit the Krilu art. The open inheritance system carried out by artists is by teaching individual studio members who are interested and want to learn Krilu musical instruments. Meanwhile, the closed system is not found in the inheritance system. The Krilu musical instrument is played when the official speech is given in the welcoming dance, and inheritance.